Deactivation of the dorsal anterior cingulate cortex indicated low postoperative sports levels in presurgical patients with chronic ankle instability - Xiao'ao Xue; Shengkun Li; Hongyun Li; Qianru Li; Yinghui Hua (BMC, 2021)
Abstract Background Injury-related fear contributed to disability in chronic ankle instability (CAI), while there still lacked exploration on the appraisal processes of the injury-related stimuli. This study aimed to compare the neural activities of the appraisal processes of sprain-related stimuli between presurgical chronic ankle instability patients and healthy controls through functional magnetic resonance imaging (fMRI) and evaluate its relationships with the clinical outcomes of orthopedic surgeries. Methods Eighteen presurgical CAI patients and fourteen healthy controls were recruited and underwent an fMRI session with visual stimulation of movies that showing typical ankle sprains accidents or control videos and the corresponding fear ratings. The clinical outcomes were collected at baseline and a minimum of 2 years after surgery; these included the American Orthopaedic Foot and Ankle Society (AOFAS) scores, the Numeric Rating Scale (NRS) scores, and the Tegner Activity Rating Scale scores. The two-sample t-test would be applied to identify which brain regions were influenced by CAI, and the correlation analysis would be applied to measure the relationship between the activation and clinical outcomes. Results Dorsal anterior cingulate cortex (dACC) was deactivated in CAI patients when compared with healthy controls, and the dACC deactivation strength revealed a moderate correlation with the values of fear ratings for all participants. The deactivation strength was negatively correlated with AOFAS at baseline, with Tegner at follow-up and its improvement. Conclusions Presurgical CAI patients presented deactivated dACC as a different neural activity of appraisal processes of sprain-related stimuli when compared with healthy controls, which was associated with lower postoperative sports levels. More comprehensive patients care including psychological interventions were needed in the clinical management of chronic ankle instability.